Autoimmunity as a Double Agent in Tumor Killing and Cancer Promotion - Toomer, Kevin H.; Chen, Zhibin (Frontiers in Immunology, 2014)
Cancer immunotherapy through manipulation of the immune system holds great potential for the treatment of human cancers. However, recent trials targeting the negative immune regulators CTLA4, PD-1 and PD-L1 demonstrated that clinically significant antitumor responses were often associated with the induction of autoimmune toxicity. This finding suggests that the same immune mechanisms that elicit autoimmunity may also contribute to the destruction of tumors. Given that the immunological identity of tumors might be largely an immunoprivileged self, autoimmunity may not represent a wholly undesirable outcome in the context of cancer immunotherapy. Rather, targeted killing of cancer cells and autoimmune damage to healthy tissues may be intricately linked through molecular mechanisms, in particular inflammatory cytokine signaling. On the other hand, since chronic inflammation is a well-recognized condition that promotes tumor development, it appears that autoimmunity can be a “double agent” in mediating either pro-tumor or antitumor effects. This review surveys the tumor-promoting and tumoricidal activities of several prominent cytokines: IFN-γ, TNF-α, TGF-β, IL-17, IL-23, IL-4, and IL-13, produced by three major subsets of T helper cells that interact with innate immune cells. Many of these cytokines exert divergent and seemingly contradictory effects on cancer development in different human and animal models, suggesting a high degree of context dependence in their functions. We hypothesize that these inflammatory cytokines could mediate a feedback loop of autoimmunity, antitumor immunity and tumorigenesis. Understanding the diverse and paradoxical roles of cytokines from autoimmune responses in the setting of cancer will advance the long-term goal of improving cancer immunotherapy, while minimizing the hazards of immune-mediated tissue damage and the possibility of de novo tumorigenesis, through proper monitoring and preventive measures.